REPUBLIC OF YEMEN: OVERCOMING SEPARATIST TRENDS - A. V. Fedorchenko (Vestnik MGIMO-Universiteta)
The article deals with ethnic and religious problems of modern Yemen. Based on the analysis of the main barriers between Yemeni societies, the author assesses the political and economic basis of separatist tendencies in the country. In the prospective part of the article the author examines the possible development of disintegration tendencies in the country. The Republic of Yemen is noted for severity and variety of domestic political, sectarian, clan challenges that still manages to soften, but are capable to split the country and lead to the establishment on its territory of the new states in the near future. Despite the fact that the change in top state leadership in Yemen after the "Arab Spring" was held on the softer model compared with Libya or Syria scenario, the transition period is not crowned with the stabilization of the political and economic situation and the onset of systemic reform. The most favorable scenario - the successful completion of a conference on National dialogue involving the main political parties and movements. This is not an easy task, given the negative attitude to this idea of the South Peace Movement and the Movement of al-Husi who are deeply involved in the conflict. Maintaining the status quo - the continuation of the armed conflict in Yemen and growth of base for international terrorism. The negative scenario - the territorial disintegration of the country. In this case, the possible are establishment of two states - South Yemen and North Yemen, as well as creation of an independent state in northern border areas adjacent to Saudi Arabia. The vast majority of the southern Yemeni officials until recently argued for its separation. Decentralization on the basis of the federal state. Separatist tendencies are gaining strength, but as a compromise the creation of a federal state should be considered. The implementation of this option is only possible as a result of peaceful national reconciliation, as well as with external support.